Molecular alterations associated with metastases of solid pseudopapillary neoplasms of the pancreas. Issue 1 (27th November 2018) - Amato, Eliana; Mafficini, Andrea; Hirabayashi, Kenichi; Lawlor, Rita T; Fassan, Matteo; Vicentini, Caterina; Barbi, Stefano; Delfino, Pietro; Sikora, Katarzyna; Rusev, Borislav; Simbolo, Michele; Esposito, Irene; et al.
Abstract: Solid pseudopapillary neoplasms (SPN) of the pancreas are rare, low‐grade malignant neoplasms that metastasise to the liver or peritoneum in 10–15% of cases. They almost invariably present somatic activating mutations of CTNNB1 . No comprehensive molecular characterisation of metastatic disease has been conducted to date. We performed whole‐exome sequencing and copy‐number variation (CNV) analysis of 10 primary SPN and comparative sequencing of five matched primary/metastatic tumour specimens by high‐coverage targeted sequencing of 409 genes. In addition to CTNNB1‐ activating mutations, we found inactivating mutations of epigenetic regulators ( KDM6A, TET1, BAP1 ) associated with metastatic disease. Most of these alterations were shared between primary and metastatic lesions, suggesting that they occurred before dissemination. Differently from mutations, the majority of CNVs were not shared among lesions from the same patients and affected genes involved in metabolic and pro‐proliferative pathways. Immunostaining of 27 SPNs showed that loss or reduction of KDM6A and BAP1 expression was significantly enriched in metastatic SPNs. Consistent with an increased transcriptional response to hypoxia in pancreatic adenocarcinomas bearing KDM6A inactivation, we showed that mutation or reduced KDM6A expression in SPNs is associated with increased expression of the HIF1α‐regulated protein GLUT1 at both primary and metastatic sites. Our results suggest that BAP1 and KDM6A function is a barrier to the development of metastasis in a subset of SPNs, which might open novel avenues for the treatment of this disease. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.